2007
DOI: 10.1159/000100004
|View full text |Cite
|
Sign up to set email alerts
|

Types of Depression More Frequent in Bipolar than in Unipolar Affective Illness: Results of the Polish DEP-BI Study

Abstract: Background: The aim of the study was to assess the relative frequency of various kinds of depression in patients with bipolar and unipolar affective illness. The study was performed in the framework of the DEP-BI project aimed at assessing the prevalence of bipolar disorders among depressive outpatients treated by psychiatrists in Poland. Methods: Eight-hundred and eighty patients (237 male, 643 female) participated in the study. The patients were classified into the following diagnostic categories: bipolar af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 48 publications
4
17
0
5
Order By: Relevance
“…Each item has 4 possible answers, ranging from 0 to 3 where 0 ¼lack of symptom and 3 ¼extreme severity of that symptom. All the symptoms of atypical depression were more severe in bipolar depression than in other subtypes of depression that may correspond to the results of our studies showing higher prevalence of such symptoms of atypical depression as hypersomnia and hyperphagia in bipolar spectrum patients compared with unipolar ones (Rybakowski et al, 2005(Rybakowski et al, , 2007. In our present study, also other features of atypical depression such as leaden paralysis and increased weight gain as well as hypersomnia, increased appetite and rejection sensitivity were more often seen in bipolar patients.…”
Section: Tablesupporting
confidence: 91%
See 1 more Smart Citation
“…Each item has 4 possible answers, ranging from 0 to 3 where 0 ¼lack of symptom and 3 ¼extreme severity of that symptom. All the symptoms of atypical depression were more severe in bipolar depression than in other subtypes of depression that may correspond to the results of our studies showing higher prevalence of such symptoms of atypical depression as hypersomnia and hyperphagia in bipolar spectrum patients compared with unipolar ones (Rybakowski et al, 2005(Rybakowski et al, , 2007. In our present study, also other features of atypical depression such as leaden paralysis and increased weight gain as well as hypersomnia, increased appetite and rejection sensitivity were more often seen in bipolar patients.…”
Section: Tablesupporting
confidence: 91%
“…In other studies, depression with atypical features (according to DSM-IV) has been estimated to be two times more likely in bipolar II than in unipolar patients (Benazzi, 2000(Benazzi, , 2003. In a Polish DEP-BI study, the most prominent symptoms of atypical depression, such as hypersomnia and hyperphagia were significantly more frequent in unipolar than in bipolar depressed patients (Rybakowski et al, 2005(Rybakowski et al, , 2007. Recently, hypersomnia has been recognized as an important clinical feature of bipolar depression (Forty et al, 2008) and some authors consider atypical depression as part of a broadly defined "bipolar spectrum" (Perugi et al, 1998(Perugi et al, , 2003Akiskal and Pinto, 1999;Akiskal and Benazzi, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…It should be also noted that in most analyses manic (BD type I) and hypomanic (BD type I and BD type II) phases are included into the same comparative group, which results in a lack of differentiation between the serious consequences of mania and potentially positive aspects of hypomania (Beentjes et al 2012). Depressive episodes also have a dissimilar course and during remission in particular BD subtypes the different subclinical symptoms may be present (Judd et al 2003, Rybakowski et al 2007). One can conclude that these issues have a significant impact on the perception of the ill life-partners by healthy spouses, and thus may be associated with dyadic adjustment as well.…”
Section: Marital Quality and Bipolar Disordermentioning
confidence: 99%
“…In particular, women with a diagnosis of Bipolar disorder (BD) have a high risk to develop a mood episode after giving birth (Freeman and Gelenberg, 2005;Leibenluft, 1996). This risk is even greater than the one reported in women with Major depressive disorder (MDD) (Kim et al, 2008;Rybakowski et al, 2007;Viguera et al, 2011). A large epidemiological study found that BD is the psychiatric illness that contributes more to a psychiatric readmission during the 12 months Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jad after childbirth (Munk-Olsen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%